The EURO, Prudent Coherence? - Ivo J.M. Arnold; Casper G. de Vries (Tinbergen Institute, 1998)
A flurry of recent articles has argued on the basis of constructed European widemonetary aggregates that the demand for EURO's will be more stable than thecurrent demand for national currencies. In policy circles this seeminglymoderating effect of monetary integration figures as an additional argument prounion. On the basis of the standard foreign exchange rate model we argue thatonce the uncoordinated country specific money supply system is abolished, thecoherence between local monetary aggregates increases dramatically, leavinglittle room for a free ride on the law of large numbers. The only road towardsstability is prudent monetary policy.
Keywords: 330; Euro; Geldnachfrage; Theorie; EU-Staaten